Three-dimensional reconstruction of ACL- injuries - Krosshaug, T.; Bahr, R. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Although the biomechanics of ACL injuries is a popular research topic, precise descriptions of the motion involved is not available. We have therefore developed a model-based image-matching technique to reconstruct human motion from uncalibrated video sequences of actual injury situations. The method has been validated against traditional 3D motion analysis system with good results [1]. The purpose of the present study was to test the applicability of the method on two different ACL injuries from different sports. Methods The first situation was a non-contact plant-and-cut injury with three different camera views (Fig. 1a). In situation two (Fig. 1b), a downhill skier suffers an ACL injury to the left leg as the right ski looses the grip, causing a wide snow-plough position. The 3D modelling program Poser provided the environment for the model matching procedure. A customized skeleton computer-model was built based on anthropometrical measurements which were obtained from each injured athlete. A computer model of the handball field was built and the Poser cameras were "calibrated" by adjusting the translation, orientation and focal length parameters for each time frame, until our field model matched the background video sequences. This was not possible with the same precision for the downhill video, since the positions of landmarks in the background were unknown. Finally, a frame-by-frame matching of the skeleton model to the athlete in the video was completed.